Implementation of Game Engineering Strategies Through Group Tutoring Services to Develop Work Ethic - Emmy Ardiwinata; Natasya Nur Rahmadania (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The large number of students who face behavioral adjustment problems impacts students' unpreparedness for work demands, even though vocational school students must have a good work ethic and be competitive. This research aims to see a picture of the effectiveness of implementing game technique strategies through group guidance services for Vocational High School (SMK) students. This research uses an experiment with a quantitative approach and a one-group pretest and post-test design. The population of this study was 85 class X vocational school students. The research was conducted using a purposive sampling technique, with the final sample size being ten vocational school students. Data collection was carried out using the student work ethic scale. The data obtained was then analyzed using descriptive and inferential statistical analysis techniques. The results of the data analysis show that a significance score of 0.005<0.05 is obtained, which means that the hypothesis is accepted. Based on these results, game techniques significantly influence the development of the work ethic of vocational school students.